Expression of TMEM40 in bladder cancer and its correlation with clinicopathological parameters - Zhang, Qing-Yan (Int J Clin Exp Pathol, 2017)
Transmembrane protein 40 (TMEM40) is a 23-kDa protein in cell membrane. There is no report that TMEM40 is associated with cancer. However, our study found that TMEM40 was high expressed in bladder cancer tissues. Immunohistochemical analyses of TMEM40 expression were performed on a tissue microarray including 72 transitional cell carcinomas and 43 normal bladder tissues to investigate the expression and clinical significance of TMEM40 in bladder cancer. We adopted receiver operating characteristic (ROC) analysis to select the optimal cut-off score. TMEM40 expression was defined positive if above 62.5% of cells were stained, and below it was negative. Then, the expression of TMEM40 in bladder cancer cells was evaluated by quantitative real-time PCR and western blot analysis. A significantly high level of TMEM40 in bladder cancer cells was proved. On the basis of ROC curve analysis, TMEM40 expression was positive in 68.1% (n=49) and negative in 31.9% (n=23) of bladder cancer cases. TMEM40 staining was positive in 2.3% (n=1) and negative in 97.7% (n=42) of normal bladder tissues. It showed that TMEM40 was up-regulated in bladder cancer tissues compared to normal bladder tissues. Moreover, TMEM40 expression was significantly associated with histological grade (P<0.05), clinical stage (P<0.05), pT status (P<0.05), but not age. Our study demonstrates that high TMEM40 expression is associated with bladder cancer, and it could be a diagnostic biomarker for bladder cancer.